Grow it right: culture, care & cytotoxicity in cell studies - Mohd Radzi, Nur Fathiah (Faculty of Pharmacy, 2025)
The Tissue Culture Unit, Faculty of Pharmacy, UiTM, successfully organised a webinar titled Grow It Right: Culture, Care & Cytotoxicity in Cell Studies on 10 September 2025 (Wednesday) via Microsoft Teams. The event was held in collaboration with Apical Scientific Sdn. Bhd. and Nacalai Tesque, Japan.